The Dynamic of e-KTP Evaluation Program in DKI Jakarta - Soemartono, Triyuni (UI Scholars Hub, 2014)
The study aims to analyze the evaluation of e-KTP program implementation. The usage of electronic identity (e-ID/e-KTP) provides several benefits for users, private institutions, and the government, hence encouraging many countries to implement such program. In 2009, Indonesia launched the e-KTP program as a National Identity Card, by pointing six districts/municipalities as a pilot project. e-KTP is a demographic document containing security or controlling system—both administration as well as information technology based on national population database. Each citizen may only have one KTP with one Resident Registration Number (NIK)—as a single identity for each resident, valid for life. In 2011, DKI Jakarta, as the capital of Indonesia, has implemented the e-KTP program. The research used qualitative method to describe the phenomenon, classify and evaluate it, by taking the administrative-village (Kelurahan) of Pondok Pinang, Kebayoran Lama Sub-district in South Jakarta and Duri Kepa, Kebon Jeruk Sub-district in West Jakarta as the case study. The result shows that the implementation of the policy still have shortages, particularly related to major resources, such as limited technical resources and human resources to operate the e-KTP program. The problems need to be evaluated in order to improve the success of dynamic and updated e-KTP program in the future.